2012
DOI: 10.1091/mbc.e11-08-0714
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative factor regulates connective tissue growth factor (CTGF/CCN2) expression in T24 bladder carcinoma cells

Abstract: Connective tissue growth factor (CTGF/CNN2) is a novel APF target gene. A novel mechanism is described by which the APF cellular receptor, cytoskeleton-associated protein 4 (CKAP4), mediates APF-induced CTGF transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Evidence confirming CKAP4's ability to function as a receptor for APF was exhibited by the use of an antibody against CKAP4 which blocked APF activity and by siRNA knockdown of CKAP4 which reduced cell sensitivity to APF. Subsequent studies confirmed the cell surface expression of CKAP4 in HeLa cells by immunolocalization of nonpermeabilized cells [14] and by cell surface biotinylation [16] and also demonstrated that CKAP4 expression was required for APF-induced cellular effects, including (1) inhibition of normal bladder epithelial cell and cervical and bladder carcinoma cell proliferation [11,[13][14][15], (2) altered gene expression (i.e., vimentin, zonular occludens-1 [ZO-1], E-cadherin, p53, MMP2, and CCN2 [13][14][15]), and (3) Akt/GSK3β/β-catenin phosphorylation [15].…”
Section: Precedence For Ckap4 Functioningmentioning
confidence: 81%
See 4 more Smart Citations
“…Evidence confirming CKAP4's ability to function as a receptor for APF was exhibited by the use of an antibody against CKAP4 which blocked APF activity and by siRNA knockdown of CKAP4 which reduced cell sensitivity to APF. Subsequent studies confirmed the cell surface expression of CKAP4 in HeLa cells by immunolocalization of nonpermeabilized cells [14] and by cell surface biotinylation [16] and also demonstrated that CKAP4 expression was required for APF-induced cellular effects, including (1) inhibition of normal bladder epithelial cell and cervical and bladder carcinoma cell proliferation [11,[13][14][15], (2) altered gene expression (i.e., vimentin, zonular occludens-1 [ZO-1], E-cadherin, p53, MMP2, and CCN2 [13][14][15]), and (3) Akt/GSK3β/β-catenin phosphorylation [15].…”
Section: Precedence For Ckap4 Functioningmentioning
confidence: 81%
“…In direct support of the idea that CKAP4 must be phosphorylated to enter the nucleus, Zacharias et al also showed by metabolic labeling with γ 32 P-ATP that nuclear CKAP4 is phosphorylated [16]. Matika et al (2012) reported similar nuclear localization of CKAP4 in response to APF in T24 bladder carcinoma cells using confocal microscopy and cellular fractionation followed by Western Blot [13]. Of significant importance in this study was the detection of a second, smaller CKAP4-specific band in the nuclear fraction of APF-treated cells, suggesting that CKAP4 may be proteolyzed prior to entering the nucleus; moreover, the detection of a relatively small amount of CKAP4 in the nucleus of untreated cells in this study and in other unpublished experiments suggests that CKAP4 may have some inherent nuclear function not related to APF-induced signal transduction or that may be specific to cancer cells, as nuclear localization of CKAP4 after binding of tPA or SPA was not apparent in previous studies [10,12].…”
Section: Ckap4 In the Nucleusmentioning
confidence: 89%
See 3 more Smart Citations